2009
DOI: 10.1021/ic801806r
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical FeWO4 Microcrystals: Solvothermal Synthesis and Their Photocatalytic and Magnetic Properties

Abstract: Highly hierarchical platelike FeWO(4) microcrystals have been synthesized by a simple solvothermal route using FeCl(3) x 6 H(2)O and Na(2)WO(4) x 2 H(2)O as precursors, where ethylene glycol (EG) plays an important role as a capping agent in directing growth and self-assembly of such unique structures. In addition, a certain amount of CH(3)COONa (NaAc) was necessary for the formation of such unique FeWO(4) microstructures. The photocatalytic property of as-synthesized hierarchical FeWO(4) microcrystals has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
121
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 206 publications
(124 citation statements)
references
References 44 publications
3
121
0
Order By: Relevance
“…Finally, further increase with reaction time 15-20 minutes leads to the formation of selfassembled hierarchical nanostructures as shown in Figure 8c-f. We observed the formation of rhombus shape nanostructure at 15 min and with a further increase in the reaction time about 20 minutes led to the dumbbell shape nanostructures formation. The formation of hierarchical nanostructure by self assembly and oriented attachment growth mechanism was also observed by different researchers [45][46]. We have reported formation of LiFePO 4 flower like hierarchical microstructure by Fig.…”
Section: Size and Morphologysupporting
confidence: 70%
See 1 more Smart Citation
“…Finally, further increase with reaction time 15-20 minutes leads to the formation of selfassembled hierarchical nanostructures as shown in Figure 8c-f. We observed the formation of rhombus shape nanostructure at 15 min and with a further increase in the reaction time about 20 minutes led to the dumbbell shape nanostructures formation. The formation of hierarchical nanostructure by self assembly and oriented attachment growth mechanism was also observed by different researchers [45][46]. We have reported formation of LiFePO 4 flower like hierarchical microstructure by Fig.…”
Section: Size and Morphologysupporting
confidence: 70%
“…Zhou et al have successfully prepared highly hierarchical plate like FeWO 4 micro-crystals by a simple solvothermal route using ethylene glycol as a capping agent [45]. It was suggested that solvent or surfactant such as ethylene glycol or oleyleamine plays an important role in directing the growth and self-assembly of such unique structures along certain growth direction.…”
Section: Wwwintechopencommentioning
confidence: 99%
“…Metal tungstates have attracted attention in the last decades since they are a fascinating class of materials that offer a large wide of technological applications, such as catalysts, 1 optics, 2 humidity sensors, 3 and magnetic, 1,4,5,6 properties. Iron tungstate (FeWO 4 ) is one of the most promising materials of this family and their electronic and magnetic properties have been studied to explore its potential applications.…”
mentioning
confidence: 99%
“…Iron tungstate (FeWO 4 ) is one of the most promising materials of this family and their electronic and magnetic properties have been studied to explore its potential applications. 1,4,7 The electronic and magnetic structures of FeWO 4 have been scarcely studied and further studies on magnetic behavior in FeWO 4 are necessary to deep understand their fundamental properties. Recently, Stüβer et al 8 and Rajagopal et al 9 reported some magnetic properties of FeWO 4 and others isomorphous transition-metal tungstates systems such as MnWO 4 , NiWO 4 , CoWO 4 indicating that these systems have an incomplete 3d shell and are paramagnetic at room temperature, while at low temperatures, these complex metal oxides undergo cooperative transitions to antiferromagnetically ordered states.…”
mentioning
confidence: 99%
See 1 more Smart Citation